Upaya Peningkatan Hasil Belajar Siswa Melalui Metode Pembelajaran Latihan (Drill) Tentang Permainan Bola Voli Di Kelas IV SD Negeri Bubulak 1 - Suhaenah, Nena (Universitas Pakuan, 2023)
EFFORTS TO IMPROVE STUDENT LEARNING OUTCOMES THROUGH THE DRILL LEARNING METHOD ABOUT VOLLEYBALL GAMES IN CLASS IV ELEMENTARY SCHOOLS (SD NEGERI BUBULAK 1)This study aims to determine the learning outcomes of students in Physical Education, Sports and Health (PJOK) lessons about volleyball games through drill models in class IV B, to find out the process of increasing student learning outcomes in PJOK subjects about ball games volleyball through the drill model in class IV B semester 2 of elementary school. The results of this study indicate that the drill learning method can be a fun variation of learning for students so that it is proven to improve student learning outcomes. Before using the drill learning method, the learning outcomes of students only reached an average score of 74.53 or 40% of all students, then there was an increase after using the drill method to 77.40 or 75% in cycle 1 and 81.40 or 100 % in cycle 2 with a minimum completeness criterion of 75, and the results of observations of student activity have increased in every aspect observed. Likewise, the observed value of teacher activity increased from an average value of 47 (87%) in cycle 1 to 52 (96%) in cycle 2 of the possible total average value to be achieved of 54 (100%). The conclusion is that the use of the drill learning method adapted to the learning material can create a pleasant learning situation so that there is an increase in student learning outcomes. Therefore, the researchers suggested that the use of the drill learning method be socialized and used as an alternative in PJOK learning on volleyball game material in schools within the Bogor City Education Office.